Tamm review: The impact of forest tent caterpillar defoliation on maple fitness and syrup production - Roberto Silvestro; Sergio Rossi; Richard Berthiaume; Éric Bauce; Tim Rademacher; Annie Deslauriers (Forest Ecology and Management, 2025)

From Roots to Leaves: Tree Growth Phenology in Forest Ecosystems - Roberto Silvestro; Annie Deslauriers; Peter Prislan; Tim Rademacher; Negar Rezaie; Andrew D. Richardson; Yann Vitasse; Sergio Rossi (Current Forestry Reports, 2025)

Higher latewood to earlywood ratio increases resistance of radial growth to severe droughts in larch - Xianliang Zhang; Hongyan Liu; Tim Rademacher (Science of The Total Environment, 2024)

Interaction of age and elevation on xylogenesis in Juniperus przewalskii in a cold and arid region - Junzhou Zhang; Xiaohua Gou; Tim Rademacher; Lijuan Wang; Yulin Li; Qipeng Sun; Fang Wang; Zongying Cao (Agricultural and Forest Meteorology, 2023)

TAMM review: On the importance of tap and tree characteristics in maple sugaring - Tim Rademacher; Michaël Cliche; Élise Bouchard; Sara Yumi Sassamoto Kurokawa; Joshua Rapp; Annie Deslauriers; Christian Messier; Sergio Rossi; Jérôme Dupras; Élise Filotas; Sylvain Delagrange (Forest Ecology and Management, 2023)

Steps to diversify priority‐setting research in conservation: reflections on de Gracia 2021 - Tommaso Jucker; Tatsuya Amano; Alexandra Bell; Emma E. Garnett; Jan Laurens Geffert; Miriam K. Guth; Andrew Hacket‐Pain; Sarah H. Luke; Hannah S. Mumby; Matheus Nunes; Tim Rademacher; David C. Rose; et al. (Conservation Biology, 2021)

Snowmelt and early to mid‐growing season water availability augment tree growth during rapid warming in southern Asian boreal forests - Xianliang Zhang; Rubén D. Manzanedo; Loïc D'Orangeville; Tim T. Rademacher; Junxia Li; Xueping Bai; Meiting Hou; Zhenju Chen; Fenghua Zou; Fangbo Song; Neil Pederson (Global Change Biology, 2019)
Boreal forests are facing profound changes in their growth environment, including warming‐induced water deficits, extended growing seasons, accelerated snowmelt, and permafrost thaw. The influence of warming on trees varies regionally, but in most boreal forests studied to date, tree growth has been found to be negatively affected by increasing temperatures. Here, we used a network of Pinus sylvestris tree‐ring collections spanning a wide climate gradient the southern end of the boreal forest in Asia to assess their response to climate change for the period 1958–2014. Contrary to findings in other boreal regions, we found that previously negative effects of temperature on tree growth turned positive in the northern portion of the study network after the onset of rapid warming. Trees in the drier portion did not show this reversal in their climatic response during the period of rapid warming. Abundant water availability during the growing season, particularly in the early to mid‐growing season (May–July), is key to the reversal of tree sensitivity to climate. Advancement in the onset of growth appears to allow trees to take advantage of snowmelt water, such that tree growth increases with increasing temperatures during the rapidly warming period. The region's monsoonal climate delivers limited precipitation during the early growing season, and thus snowmelt likely covers the water deficit so trees are less stressed from the onset of earlier growth. Our results indicate that the growth response of P. sylvestris to increasing temperatures strongly related to increased early season water availability. Hence, boreal forests with sufficient water available during crucial parts of the growing season might be more able to withstand or even increase growth during periods of rising temperatures. We suspect that other regions of the boreal forest may be affected by similar dynamics.

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

Evaluation of climate‐related carbon turnover processes in global vegetation models for boreal and temperate forests - Martin Thurner; Christian Beer; Philippe Ciais; Andrew D. Friend; Akihiko Ito; Axel Kleidon; Mark R. Lomas; Shaun Quegan; Tim T. Rademacher; Sibyll Schaphoff; Markus Tum; Andy Wiltshire; et al. (Global Change Biology, 2017)
Turnover concepts in state‐of‐the‐art global vegetation models ( GVM s) account for various processes, but are often highly simplified and may not include an adequate representation of the dominant processes that shape vegetation carbon turnover rates in real forest ecosystems at a large spatial scale. Here, we evaluate vegetation carbon turnover processes in GVM s participating in the Inter‐Sectoral Impact Model Intercomparison Project ( ISI ‐ MIP , including HYBRID 4, JeDi, JULES , LPJ ml, ORCHIDEE , SDGVM , and VISIT ) using estimates of vegetation carbon turnover rate ( k ) derived from a combination of remote sensing based products of biomass and net primary production ( NPP ). We find that current model limitations lead to considerable biases in the simulated biomass and in k (severe underestimations by all models except JeDi and VISIT compared to observation‐based average k ), likely contributing to underestimation of positive feedbacks of the northern forest carbon balance to climate change caused by changes in forest mortality. A need for improved turnover concepts related to frost damage, drought, and insect outbreaks to better reproduce observation‐based spatial patterns in k is identified. As direct frost damage effects on mortality are usually not accounted for in these GVM s, simulated relationships between k and winter length in boreal forests are not consistent between different regions and strongly biased compared to the observation‐based relationships. Some models show a response of k to drought in temperate forests as a result of impacts of water availability on NPP , growth efficiency or carbon balance dependent mortality as well as soil or litter moisture effects on leaf turnover or fire. However, further direct drought effects such as carbon starvation (only in HYBRID 4) or hydraulic failure are usually not taken into account by the investigated GVM s. While they are considered dominant large‐scale mortality agents, mortality mechanisms related to insects and pathogens are not explicitly treated in these models.